Current survey of early childhood intervention services in infants and young children with sex chromosome aneuploidies. Issue 2 (25th May 2020) - Thompson, Talia; Howell, Susan; Davis, Shanlee; Wilson, Rebecca; Janusz, Jennifer; Boada, Richard; Pyle, Laura; Tartaglia, Nicole
Abstract: Sex chromosome aneuploidies (SCAs) are the most commonly occurring aneuploidies in children with a collective prevalence rate of 1 in 500 live births. Prior research has documented SCAs are associated with an increased risk for early expressive language and gross motor delays, learning disorders, ADHD, autism spectrum disorder, anxiety, and executive function problems. Although SCAs have been historically underdiagnosed in young children, recent advances in noninvasive prenatal testing have resulted in an increasing nationwide cohort of infants with confirmed diagnoses. Consequently, early childhood support systems must prepare for an influx of children with known risks for associated developmental delays and potential school problems. This national survey aimed to update our understanding of current early childhood intervention services for young children with SCA in the United States and to describe parent perspectives and priorities. Descriptive statistics, chi‐square tests, and logistic regression models controlling for parent education revealed a majority of respondents reported receiving public early childhood intervention services with speech therapy as the most common service. There were significant differences in early childhood intervention services by timing of diagnosis (prenatal vs. postnatal), number of sex chromosomes (trisomy vs. tetra/pentasomy), and geographic location. Parents described interventions as desirable and effective yet also difficult to obtain due to issues with the SCA phenotype, lack of provider knowledge, and challenges navigating the intervention systems. Results support the need for enhanced provider training in SCAs, policy change for early childhood intervention qualification criteria for SCA conditions, and collaboration between medical and early childhood settings.